2015
DOI: 10.1002/adom.201500141
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Emitting Dipole Orientation with Methyl Substituents on Main Ligand of Iridium Complexes for Highly Efficient Phosphorescent Organic Light‐Emitting Diodes

Abstract: the heteroleptic molecular structure of the Ir (III) complexes and strong Coulombic interaction between the dopant and host molecules are the driving forces of the preferred EDO. [ 4,5 ] In this regard, the structure of the emitting molecules, as well as the organic host molecules, must infl uence the EDO. The effect of the ancillary ligands in the heteroleptic Ir complexes (HICs) on the EDO and the photoluminescence quantum yields (PLQY) in doped fi lms were reported recently, exhibiting that bis(phenyl-pyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…2a, b . Three heteroleptic iridium complexes of Ir(ppy) 2 tmd, Ir(3′,5′,4-mppy) 2 tmd 18 , and Ir(dmppy-ph) 2 tmd 19 possessing high Θ values were adopted to investigate the effect of the phosphor molecular structure. The molecular C 2 symmetry axis toward the center of the ancillary ligand from the origin located at the Ir atom was set as m z , the orthogonal vector to m z normal to the molecular Ir-O-O plane was set as m x , and m y was determined by a cross product of m z and m x in the dopants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a, b . Three heteroleptic iridium complexes of Ir(ppy) 2 tmd, Ir(3′,5′,4-mppy) 2 tmd 18 , and Ir(dmppy-ph) 2 tmd 19 possessing high Θ values were adopted to investigate the effect of the phosphor molecular structure. The molecular C 2 symmetry axis toward the center of the ancillary ligand from the origin located at the Ir atom was set as m z , the orthogonal vector to m z normal to the molecular Ir-O-O plane was set as m x , and m y was determined by a cross product of m z and m x in the dopants.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly enough, it is only in recent years has attention turned to the orientation of emitting dipoles of iridium-based phosphors, the most verified light-emitting dyes with high photoluminescence quantum yield and variety of chromatic spectrum as doped in the emissive layers; probably because their iridium-centered spherical shape and the amorphous surrounding nature in the emissive layers are far from having strong molecular alignments. Recently, some heteroleptic Ir complexes exhibiting efficient electroluminescence in organic light-emitting diodes are reported to possess preferred horizontal emitting dipole orientations (EDOs) 13 16 , 18 20 . However, it was difficult to assert the reason why the spherical-shaped phosphors have a propensity toward preferred molecular alignment in the emissive layers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have suggested that simultaneous host and dopant interactions in aligned matrices arise from the formation of donor/host aggregates based on the component electrostatics 22,29,30 . The complexes studied here have very similar electrostatic surfaces (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Past reports have speculated that large dipole moments present in the tris-cyclometalates lead to aggregation that suppresses dopant interactions with the host matrix 16,[26][27][28] . Other reports have proposed electrostatic interactions between electronegative regions in the (C ∧ N) 2 Ir(O ∧ O) complexes and electropositive host structures give rise to macroscopic order and thus dopant (and host) alignment 22,29,30 . We will show that neither the dopant dipole-based mechanism nor component electrostatics adequately describe the alignment process and propose a mechanism based on the inherent asymmetry of (C ∧ N) 2 Ir(O ∧ O) and some fac-Ir(C ∧ N) 3 complexes that explain the many instances of observed dopant alignment in amorphous host materials.…”
mentioning
confidence: 97%
“…It is worth noting that for simple fluorescent emitters, a maximum theoretical efficiency of ~5% is expected. 15 Peak η EQE values for all three compounds are realized for devices having an emissive layer composition of 20% of 10 . This does not correlate directly with the PL efficiency η PL , which increases monotonically with dilution, likely reflecting a role played by the emitter in charge transport.…”
mentioning
confidence: 99%